Jenis-Jenis Burung di Perkebunan Kelapa Sawit PT. Andalas Wahana Berjaya (AWB), Kabupaten Dharmasraya, Sumatera Barat - Efrita Ruswenti; Wilson Novarino; - Rizaldi (Jurnal Biologi Universitas Andalas, 2014)
Bird species at oil palm plantation of PT. Andalas Wahana Berjaya (AWB), Dharmasraya, West Sumatra, have been studied from January to February 2014. This study aimed to identify bird species at the location. We  used direct observation method and mist netting. The result found 43 bird species, which belong to 21 families and 9 orders. Those 32 species were identified through direct observation, and 16 species through mist netting, while 5 species were confirmed through both direct observation and mist netting. Among the total, 5 bird species were protected and 2 were endemic.Keywords : bird species, directly observation method, mist netting, oil palm plantation.